2006
DOI: 10.1016/j.actamat.2006.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces within strain gradient plasticity: Theory and experiments

Abstract: In this paper, it is shown that the occurrence of dislocation pileups across grain boundaries, as well as subsequent emission to the adjacent grains, is captured theoretically by gradient plasticity and confirmed experimentally by nanoindentation. From a theoretical point of view, this is accomplished (within a deformation theory framework applicable to continued loading) by accounting for a specific interfacial term in the overall potential of the material, in terms of which its response, taken to conform to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 19 publications
5
74
0
1
Order By: Relevance
“…This result avoids the complication of having to differentiate expression (20) numerically. In addition to estimating the effective response, it is of interest to estimate the statistics of the plastic strain field.…”
Section: 21mentioning
confidence: 96%
See 4 more Smart Citations
“…This result avoids the complication of having to differentiate expression (20) numerically. In addition to estimating the effective response, it is of interest to estimate the statistics of the plastic strain field.…”
Section: 21mentioning
confidence: 96%
“…An estimate for the effective response of the composite can be obtained by differentiating (20), in accordance with (12). By following similar arguments to those of [23], it can be shown that…”
Section: 21mentioning
confidence: 99%
See 3 more Smart Citations